Does short-termism influence the market value of companies? Evidence from EU countries - Małgorzata Janicka; Aleksandra Pieloch-Babiarz; Artur Sajnóg (Journal of Risk and Financial Management, 2020)
This paper fits into the stream of current research on the concept of short-termism and its importance for economic sustainability, especially sustainable finance. Short-termism focuses on short time horizons by both corporate managers and the financial markets, and prioritizes short-time shareholder return over the long-term growth of the company's value. This study engages the short-termism discussion by examining the effect of quarterly reporting on the long-term market value of listed companies. The aim of the article is to determine whether European companies experience the negative effects of short-termism, precisely, whether public companies that prepare quarterly reports, and which focus mainly on achieving the short-term goals of stock exchange investors, are seeing a decline in their market value in the long-term. We have not proven the existence of such a dependence, the increase in reporting frequency of public companies does not contribute to a decline in their long-term market value. In the case of the EU-15 the results of regression model estimation indicate a positive and statistically significant impact of the time of regular quarterly reporting on the buy-and-hold rates of return, in the “new” EU member states this relationship is not observed.
Keywords: 330; EU countries; market value of companies; quarterly reporting; short-termism; sustainable finance